Answer:
76 ounces
Step-by-step explanation:
I'm assuming you meant:
5lb+7oz-11oz=
16 ounces in a pound
5lb+7oz-11oz=
80+7-11=
87-11=
76 ounces
Answer:
y = 2x^2 - 12x + 27
Step-by-step explanation:
<u>Step 1: Distribute the power</u>
y = 2(x - 3)² + 9
y = 2(x^2 - 6x + 9) + 9
y = 2x^2 - 12x + 18 + 9
y = 2x^2 - 12x + 27
Answer: y = 2x^2 - 12x + 27
Answer:
Step-by-step explanation:
nth term = a +(n-1)d
a3 = 116 ; a + 2d = 116 ---------(i)
a7 = 180; a + 6d = 180 -------(ii)
multiply (ii) by -1. so a will be eliminated
a + 2d = 116 ---------(i)
(ii)*-1 <u>-a - 6d = -180</u> -------(ii) { Now add the two equations}
- 4d = -64
d = -64/-4
d = 16
Plug in the value of d in equation (i),
a + 2*16 = 116
a + 32 = 116
a = 116 - 32
a = 84
12th term = 84 + 11* 16 = 84 + 176 = 260
Better hearing and better sound censory
i think anyways
The answer is one hundred seventeen over three hundred twenty or 117/320